2023
DOI: 10.37934/progee.24.1.1121
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to green building implementation in Malaysia: A systematic review

Abstract: In recent years, green building has been a trend in the world. Green building in Malaysia is still lagging in terms of development in green building. The construction industry has contributed the greatest percentage of greenhouse gas emissions. In order to reduce this issue, the increase in implementing green buildings is a concern among different construction stakeholders. The aim of this study is to investigate the barriers to implementing green buildings in Malaysia. A systematic review was used to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Moreover, this matter is very important as it is strongly supported by past studies that found online platforms enhance students' performance and also help students understand the subjects or courses they take [45][46][47]. There are also previous studies emphasizing the importance of looking into the future regarding the use of technology that has a significant impact on daily life [48,49].…”
Section: Collapsing Context -Tiktok University Students and Educationmentioning
confidence: 93%
“…Moreover, this matter is very important as it is strongly supported by past studies that found online platforms enhance students' performance and also help students understand the subjects or courses they take [45][46][47]. There are also previous studies emphasizing the importance of looking into the future regarding the use of technology that has a significant impact on daily life [48,49].…”
Section: Collapsing Context -Tiktok University Students and Educationmentioning
confidence: 93%
“…According to Ifeanyichukwu et al (2021), green architecture lessens the harmful effects of construction operations. According to Yee et al (2020), it includes the 3 Rs (reduce, reuse and recycle) through environmentally beneficial methods.…”
Section: Literature Review 21 An Overview Of Green Buildingmentioning
confidence: 99%
“…Abraham and Gundimeda (2018) categorised four (4) main barriers as policy and market barriers (PMB), financial and economic barriers (FEB), information, promotion and education barriers (IPE) and managerial and organisational barriers (MOB). More recently, Yee et al (2020) grouped the challenges as internal challenges (management factors) and external challenges (market and government incentives).…”
Section: Challenges In Green Building Development In Nigeriamentioning
confidence: 99%
“…According to the study in Yee et al, (2020), construction firms will face severe problems because of their staff not being fully educated on this concept. There is a lack of market understanding and demand regarding green building (Masia et al, 2020).…”
Section: Lack Of Knowledge and Awarenessmentioning
confidence: 99%